Tubulin and actin topology during zygote formation of Saccharomyces cerevisiae - Hasek, J; Rupes, I; Svobodová, J; Streiblová, E (Journal of general microbiology, 1987)
The topology of tubulin and actin during mating of Saccharomyces cerevisiae was analysed by fluorescence microscopy with the monoclonal anti-tubulin antibody Tu01 and rhodamine-labelled phalloidin. Preconjugatory cells displayed an asymmetric distribution of the microtubule and actin cytoskeleton and an overall polarization of the cells preceding cell fusion. Prior to karyogamy, the haploid spindle pole bodies were associated with abundant cytoplasmic microtubules. Budding zygotes revealed the same tubulin and actin patterns as vegetative cells. Treatment of the mating mixture with the microtubule inhibitor nocodazole (10 micrograms ml-1) did not prevent polarization and fusion of haploids, zygote formation and emergence of the first zygotic bud. In marked contrast, the migration of the nucleus in preconjugatory cells as well as nuclear migration and fusion within the zygotes was unequivocally blocked by the action of the drug. It is suggested that the problem of the morphogenesis of mating should be approached by considering interactions at the cell periphery.
Keywords: Saccharomyces cerevisiae; Cell Cycle; zygota; aktiny; konjugace genetická; tubulin; Tubulin; fluorescenční mikroskopie; Actins; Nocodazole; benzimidazoly; Microscopy, Fluorescence; nokodazol; Benzimidazoles; Conjugation, Genetic; buněčný cyklus; Zygote